(untitled) (PRÁXIS EM SAÚDE, 2025)
The Therapeutic Follow-Up (TF) clinic aims to eliminate asylums and restore freedom, citizenship, and the right to life for patients with a mental health diagnosis. Objectives: Aiming to demystify an exclusive form of treatment, the objective was to present a clinical case still in treatment through TF. Method: For this purpose, the selected method was an experience report based on the meetings between the patient and the therapeutic companion in Uberlândia-MG from 2019 to the present. Instruments included field diaries and free-flow notes. Results: Through a brief historical overview of the clinical case, it was possible to observe the influence and power of receiving legitimate support, affection, and care from a family member and the therapeutic companion; encouragement of skill development; partnership between the therapeutic companion and family member; and active participation in the treatment offered by CAPS as an unconventional mental health intervention. Conclusion: The objective of demystifying the use of an exclusive form of treatment was achieved, as an alternative approach was demonstrated and the need to critically reflect on the treatment offered to those who require help, support, affection, and secure attachment—not just hospitalization, restraint, and medication—was highlighted.